Effort-Reward-Imbalance, Burnout, and Depression Among Psychiatrists 2006 and 2016-Changes After a Legislative Intervention - Beschoner, Petra; von Wietersheim, Jörn; Jarczok, Marc N.; Braun, Maxi; Schönfeldt-Lecuona, Carlos; Viviani, Roberto; Jerg-Bretzke, Lucia; Kempf, Maximilian; Brück, Aniela (Frontiers in Psychiatry, 2021)
Background: Physicians, especially psychiatrists, have a high risk of job-related stress, and mental impairment. In our study we examined changes in private and occupational stress factors and mental health within a decade. The legislative reduction of physicians' working hours in Germany during this period made it possible to investigate the impact of working hours in particular. Methods: Questionnaires were administered at two psychiatrist meetings (2006 and 2016) about job and family situation, depressiveness, burnout and effort-reward imbalance. A total of N = 1,797 datasets were analyzed. Results: Working hours and free weekends were associated with mental health indices. Correlation analyses showed that a reduction in weekly working hours and working days at weekends was related to reduced scores for effort-reward-imbalance, burnout and depression. Conclusions: Our data show changes in workplace stress and mental health in psychiatrists in a decade in which a reduction in working hours has been required by law. These results can provide indications of effective prevention strategies in the professional context of physicians working in psychiatry.